The Role of the Indonesia Deposit Insurance Corporation (LPS) in Mitigating Systemic Risk - Anatia Agusti; Yonna Anggayu Putri; Berta Agus Petra (GOVERNORS, 2026)
The increasing number of Rural Bank (BPR) failures in Indonesia has raised concerns regarding depositor confidence and regional financial stability, highlighting the strategic role of the Indonesia Deposit Insurance Corporation (LPS) in mitigating systemic risk. This study aims to examine how LPS contributes to maintaining financial stability through the resolution of failed rural banks by analysing the cases of PT BPR Sembilan Mutiara and PT BPR Lubuk Raya Mandiri in West Sumatra. A qualitative case study based on documentary analysis was employed using official reports, regulatory documents, and other credible secondary sources related to bank resolution and deposit insurance. The findings indicate that the failures of both BPRs were primarily driven by weak corporate governance, inadequate capital management, declining liquidity, and ineffective risk management, while LPS effectively mitigated regional systemic risk through timely deposit reimbursement, coordinated bank resolution, and institutional collaboration with financial authorities. Beyond reimbursing insured deposits, LPS contributed to maintaining depositor confidence, supporting orderly bank resolution, and reducing the potential contagion effects arising from rural bank failures. The study concludes that strengthening corporate governance, early intervention mechanisms, institutional coordination, and public financial literacy is essential for enhancing the effectiveness of LPS and reinforcing the resilience of Indonesia's banking system.